The Correlation of I'jaz Bayani with Scientific Signals in the Story of Maryam: A Study of the Miracles of Language and Science in the Qur'an - Nurhayat, Tasya Putri; Fathurrohman, Asep Ahmad; Zulaiha, Eni (UIN Sunan Gunung Djati Bandung, 2025)
This research aims to study the correlation between i’jaz bayani and scientific hints in the story of Maryam in the Qur’an. Using a language and science approach, this research analyzes the choice of diction, sentence structure, and word use in Surah Maryam, which shows the miracle of the language of the Qur'an. The main focus of this study is the use of the word